"Mini Bow" a strategy to develop the capacity of logical reasoning, reading comprehension and creativity in students from elementary level - Freire Pazmiño, Julio César (SATHIRI, 2020)
The mini bow as methodologic strategy in the teaching and learning process was realized in Orellana’s province, it has as objective help to strengthen education, knowledge through logical reasoning, reading comprehension, leading to creativity. Directed to students of basic education, it permitted to generate significant learnings that lead to form critical, reflective, purposeful, creative students, with the capacity to solve their problems and the society as well, to achieve manage to function efficiently and effectively in their educational life, solving in a practical way the various academic difficulties that contribute to the socioeconomic and cultural development of society in general. An approach was used that allows to deepen the meanings, contextualize and interpret correctly the results. We worked with ninety five students of the eighth level of basic education of the Indoamérica Technological University who participated in bonding, the same ones who in order to obtain the data in the process undertook actions with the students where they carried out their professional practices such as diagnostic evaluation, application of the mini bow strategy and the final evaluation that allowed to develop skills, capabilities and specifically competencies, to create studies habits in an active and participating way, achieving significant knowledges in their subjects and in the most important to contribute to the human being development and social service as well. The mini bow is a didactic game with German origin that achieve to stimulate the logical thinking, the abstraction capacity and good mental concentration, working in a collaborative way, autonomous and experimental practical.